Fish powder in instant fish soup mix (Journal of the Bangladesh Agricultural University, 2012)
This study was conducted with the development of instant fish soup mix and finding out the effect of fish powder on it. Ingredients of soup mix were cooked and dried up to desired moisture content. The drying or dehydration was done by using  a mechanical dryer (Cabinet dryer) at constant air flow rate and constant temperature with varying thicknesses. After drying  the dried products were ground to make powder. These were then mixed with desired composition. Here fish powder was  varied in composition in different samples and it was 5%, 10% and 15% in Mix-1, Mix-2 and Mix-3 respectively. For  preparing soup mix was reconstituted with boiled water. The result of organoleptic test was determined by ANOVA and  DMRT analysis to find out the best sample. (Mix-2) was adjudged to be the best by the panelists using 1-9 hedonic scale   and ranked as like very much securing score 8.0 which containing 10% fish power.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12106   J. Bangladesh Agril. Univ. 10(1): 145148, 2012